Analysis of anatomical location, mitoses, and Ki-67 in 2608 meningiomas - Broechner, Anders; Maier, Andrea Daniela; Mirian, Christian; Sahm, Felix; Hamelmann, Stefan; Ratliff, Miriam; Etminan, Nima; Herold-Mende, Christel; Krieg, Sandro; Deimling, Andreas von; Maas, Sybren L N; Bos, Eelke M; et al. (Journal of neuropathology and experimental neurology, 2025)
Ki-67 proliferation index (PI) and mitoses are frequent histopathological proliferation markers in meningioma diagnostics. They are used extensively in grading, with mitotic count constituting the major grading criterion in meningiomas but their mutual correlations and associations with phenotypic characteristics are incompletely known. We addressed this by investigating a large retrospective meningioma cohort. We investigated global Ki-67, Ki-67 hotspots, and mitoses, and their associations with WHO grades, histological subtypes, and anatomical locations in 2608 meningiomas from Heidelberg and Mannheim University Hospitals in Germany. As expected, higher WHO grades and inherent subtypes had higher proliferation indices although the variance was high. The transitional subtype had higher proliferation indices than other grade 1 histologies. Skull base meningiomas had significantly lower global Ki-67 PI compared to convexity meningiomas also when stratified for WHO grade. Focal increases of Ki-67, here dubbed hotspots morphology, were more prevalent in higher WHO grades, indicating potential aggressive tumor subclones. Utilizing K-means clustering on paired Ki-67 PIs and mitoses improved alignment with WHO grades. Our analysis identified a heterogenous group of tumors in which certain locations and subtypes were associated with increased Ki-67 PI. They suggests that considering both mitoses and Ki-67 indices improves alignment with WHO grade.
Veröffentlicht: 20. November 2025
Gesehen am 28.01.2026